Effectiveness of Performance Management System for Employee Performance Through Engagement. (October 2020) - Awan, Sajid Hussain; Habib, Nazia; Shoaib Akhtar, Chaudhry; Naveed, Shaheryar
This article seeks to explore the effectiveness of a comprehensive performance management system in terms of employee performance. Besides, the mediating effect of work engagement was also examined. The performance management system effectiveness (PMSE) was determined by the extent of its accuracy and fairness, as recommended by previous researchers. A sample of 285 employees was selected from various branches of private banks located across Pakistan. A structured questionnaire was used, which was validated through confirmatory factor analysis (CFA) in the Pakistani context. The results indicated a significant impact of PMSE and work engagement on task and contextual performance of employees. Also, complementary mediation of employee work engagement in the relationship between PMSE and employee performance (in terms of task and contextual performances) was also supported. The findings of the research are helpful for the development of HR and PMSE strategy in the private banks of Pakistan. The study also suggests that a comprehensive PMSE model including the perception of fairness as a mandatory part, may be introduced for employees' enhanced work engagement and task/contextual performance. The mediating relationship of work engagement has established the process of PMSE for the task and contextual performances of employees, which is a valuable contribution of the study.